Contributions to the geological map of Sierra de Perijá, Colombia (2023)
Cartographic review of previous literature and recent paleontological findings (Rincón, 2022; Orozco, 2022, TDG) demonstrate the need for an update of the geological map for the Manaure area, Cesar, Colombia. Based on the map by Forero (1972), the Colombian Geological Survey (2015), INGEOMINAS (2010), and fieldwork conducted in Manaure in 2022, a contribution to the geological map of the Sierra de Perijá is made. An area of 360.79 km2 was covered, passing through Manaure and San José de Oriente (in the field), and La Paz and El Plan (based on literature). Approximately 465.57 km of contacts were traced in the field and using Google Earth, along with the completion of around 26 field stations and the collection of 146 structural data points. This map shows the angular unconformity between the Mesozoic and the metamorphic basement present at the western mountain front of the Sierra de Perijá next to Manaure (Sardinata Fault). Beyond this basement, ascending the mountain, Devonian-Permian periods are encountered. According to a geological cross-section obtained from the map, it is contemplated that the uplift of the entire Mesozoic, in thrust sheets and duplex, may have been caused by the influence of the Cerrejón Fault at depth. The map includes what is believed to be the Colón Formation, La Luna Formation, Cogollo Group, Río Negro Formation, and La Quinta Formation for the Mesozoic era.